The perils of oil price and exchange rate movement on KLCI / Noor Zahirah Mohd Sidek...[et al.] - Mohd Sidek, Noor Zahirah; Laidin, Jamilah; Ismail, Shahiszan (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Oil price, exchange rate and the stock market reaction are among the longest standing issues in empirical economics especially for oil exporting countries. The main objective of this study is to detect asymmetric effect in both the long-run as well as in the short-run. The finding, obtained by means of a NARDL model from January 1990 to December 2016 by using monthly data of Malaysia, indicates that in the bound test, the NARDL specification has suggested the existing of cointegration among variables, including the oil price, Industrial Production Index (IPI as a proxy to national income) and exchange rate. Bound test shows all variables cointegrated in the long run by F-stat exceed the critical upper bound. The estimated NARDL model has affirmed the presence of asymmetric in the long run for all variables. It is notified that the asymmetric long run relation between stock market and oil price, considering the increase and decrease of the oil price, is significantly related to the stock market. Exchange rate also indicates similar result, with both directions significantly affect the stock market. Thus, policy attention should be directed to sharpen market power and investment behaviours in Malaysia.